IMPLEMENTASI MEDIA PEMBELAJARAN DIGITAL SAD KERTI PADA TK DWIJENDRA DENPASAR - I Nyoman Agus Suarya Putra; Putu Gede Surya Cipta Nugraha; Ni Wayan Wardani (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
The Bali provincial government is focusing on improving education based on local wisdom, specifically Nangun Sad Kerti Loka Bali. Sad Kerti, which means six efforts to maintain the balance of the universe, is used in early childhood education. However, traditional methods, such as oral knowledge and teacher demonstrations, are not effective in conveying local wisdom. To address this, a community service activity has been introduced using Sad Kerti digital learning media, focusing on the story of Dang Hyang Nirartha. The activity uses demonstration, storytelling, and question-and-answer sessions. Teacher and student assessments were conducted, and it was found that Sad Kerti learning media is suitable for formulating learning objectives that meet student needs. This digital Sad Kerti learning media is highly feasible for use, as it helps children develop a deeper understanding of their identity and cultural heritage.